ASSESSMENT OF LIQUEFACTION RISK WITH UNIDENTIFIED SEISMIC PARAMETERS FOR NEWLY-DISCOVERED FAULTS: NUMERICAL ANALYSIS (GEOMATE Journal, 2024)
Earthquakes can trigger liquefaction, which can cause soil to lose its strength and stability. Ambon City is vulnerable to large earthquakes owing to tectonic movements. Therefore, accurate analyses are required to assess the seismic hazards and liquefaction potential. This study aims to determine the hazard spectrum and artificial earthquakes to estimate liquefaction potential through numerical analysis. This study conducts a comprehensive analysis to accurately investigate liquefaction potential using deterministic seismic analysis based on new faults and nonlinear analysis with a two-dimensional finite element approach. The results of this study show that nonlinear analysis can effectively account for the increase in pore water pressure (PWP) during earthquake shaking, thus providing more detailed information on the changes in effective stress and PWP in different soil layers. The effective stress did not decrease in the unsaturated soil layers. However, in the saturated soil layers, the effective stress decreased as PWP increased during the shaking period. Liquefaction potential was predicted before the earthquake in soils with N-SPT